Pengaruh Cultularry Resposive Teaching (CRT) Terhadap Motivasi Belajar Peserta Didik pada Materi Passing Bawah Permainan Bola Voli di SMA N 2 Semarang - Kurniawan, Bagas Indra; Zhannisa, Utvi Hinda; Waskitho, Tutur Lukas (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Education is one of the important factors in human life to provide provisions for life through various learning processes, including physical education, sports, and health learning. However, physical activity in children is still relatively low, which is a global problem, one of which is the lack of motivation of children in exercising. For this reason, a study was conducted that applied the Culturally Responsive Teaching (CRT) approach in learning to pass down in volleyball. This study aims to find out the extent to which this approach can increase students' learning motivation. This research was carried out at SMA N 2 Semarang using the classroom action research method (PTK), which was carried out in two cycles. The subject of the study is students in grades X-10 at the school. The results showed that in the first cycle, the students' learning motivation was recorded with an average score of 120.27, and experienced a significant increase in the second cycle to 141.92, with an increase of 18%. Based on these findings, it can be concluded that the application of the Culturally Responsive Teaching (CRT) approach in class X-10 SMA N 2 Semarang is effective in increasing students' learning motivation in PJOK subjects. Therefore, the CRT approach can be recommended as an alternative in PJOK learning.